2019
DOI: 10.1038/s41598-019-53114-4
|View full text |Cite|
|
Sign up to set email alerts
|

Insufficient production of IL-10 from M2 macrophages impairs in vitro endothelial progenitor cell differentiation in patients with Moyamoya disease

Abstract: Moyamoya disease (MMD) is well known to be caused by insufficient cerebral vascular formation. However, the essential pathogenesis has not yet been identified. Using our recently developed technique of generating vasculogenic and anti-inflammatory cultures, we investigated endothelial progenitor cell (EPC) expansion and differentiation under the cytokine milieu generated by the peripheral blood mononuclear cells (PBMNCs) of the operated and non-operated MMD patients. EPC colony forming assay of the cultured PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Cytokines are an important element of the immune system. Cytokines regulate the intercellular and intersystemic interactions that determine the cell viability, stimulate or suppress the cell growth, differentiation, functional activity, and apoptosis, and ensure the concerted functions of the immune, endocrine, and nervous systems in normal conditions and in response to pathological factors [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines are an important element of the immune system. Cytokines regulate the intercellular and intersystemic interactions that determine the cell viability, stimulate or suppress the cell growth, differentiation, functional activity, and apoptosis, and ensure the concerted functions of the immune, endocrine, and nervous systems in normal conditions and in response to pathological factors [46].…”
Section: Discussionmentioning
confidence: 99%
“…The IL-10 and IL-17 levels tended to change in response to administration of MAA (co)polymers. Both of the cytokines are known to play a dual role in the tumor process according to published data [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…HGF also stimulates proteoglycan synthesis and cell migration, thus, offering critical functions for cartilage growth and an outlook on the potential role of mSVF in this repair context [39]. The pronounced expression of IL-10 in eSVF and mSVF is another promising aspect with potential clinical significance, as this mediator regulates extracellular matrix formation and differentiation of EP [54,55]. Data on IGF-1 and PDGF-bb gave further indications on the potential role of eSVF and mSVF in supporting cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found that endothelial progenitor cells were mainly acted in the process of angiogenesis, while monocyte chemoattractant protein-1, tumor necrosis factor (TNF) and vascular endothelial growth factor were involved in the activation of endothelial progenitor cells [11][12][13] .Keratinocytes, dendritic cells, and T lymphocytes mediate immune responses in psoriasis, in which cytokines IL-6, IL-17, IL-23, and TNF are directly involved [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%